2022
DOI: 10.53790/aemr.v2i2.34
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Price and Exchange rate Hedging Elasticity of Cryptocurrency Demand in Nigeria

Abstract: This study examined the price and exchange rate hedging elasticity of cryptocurrency demand in Nigeria. To achieve the objective, the study employed Autoregressive Distributed Lag (ADRL) model to estimate both the short-run and long-run response of demand to changes in crypto price, consumer income and exchange rate. The Study found among others that cryptocurrency is demanded as a financial asset (either as money for exchange purpose or asset for speculative purpose). It was discovered that cryptocurrency pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Furthermore, Levulytė and Šapkauskie (2021) pointed out that the number of settlement points should be high enough for an instrument to serve as a medium of exchange. For example, Bitcoin is enjoying significant growth in acceptance and usage in El Salvador (Gupta et al 2020;Joseph et al 2022).…”
Section: Cryptocurrency As Money Commodity or Financial Instrumentmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, Levulytė and Šapkauskie (2021) pointed out that the number of settlement points should be high enough for an instrument to serve as a medium of exchange. For example, Bitcoin is enjoying significant growth in acceptance and usage in El Salvador (Gupta et al 2020;Joseph et al 2022).…”
Section: Cryptocurrency As Money Commodity or Financial Instrumentmentioning
confidence: 99%
“…Research has also suggested that cryptocurrency must gain wider acceptance as a means of global exchange to be qualified as money (Wolla 2018;Jareño et al 2020). Whether cryptocurrency is money or a financial instrument, Joseph et al (2022) argued that cryptocurrency is essentially a financial instrument because money is a highly liquid financial asset.…”
Section: Cryptocurrency As Money Commodity or Financial Instrumentmentioning
confidence: 99%
See 3 more Smart Citations